MEDIASI SENGKETA PERCERAIAN DI PENGADILAN AGAMA BENGKULU KELAS IA (STUDI ANALISIS PENERAPAN PERATURANMAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1 TAHUN 2016) - Nanang Juanda (IAIN Bengkulu, 2017)
Mediation is a peaceful, effective, and effective means of resolving disputes and may open broader access to the Parties to obtain satisfactory and just dispute resolution. The problem in this research is how the application of Supreme Court Regulation of RI. No. 1 of 2016, in optimizing the peace efforts in divorce disputes in Bengkulu Class IA Religious Court, and what are the constraints of Mediator in conducting mediation of divorce dispute in Bengkulu Class IA Religious Court. Problem solving is done through a normative juridical approach. To analyze the implementation of mediation in Religious Courts Bengkulu Class IA conducted by examining library materials or secondary data related to mediation. While the method used is descriptive research method analysis of mediation theories and the implementation of mediation in the Religious Courts by describing the case under investigation, based on the relationship between theory and reality in the field. Implementation of mediation in Bengkulu Class IA religious court, broadly divided into 4 (four) stages, namely: 1). Case registration stage, 2). Mediator stipulation stage, 3). Implementation stage of Mediation and 4). The final stage of mediation. Factors influencing the success of mediation in Bengkulu Class IA Religious Court are aspects of mediator, sociology aspect, psychology aspect, moral and spiritual aspect and good faith of the parties. While the factors inhibiting the success of mediation is the strong desire of the parties to divorce, has become a prolonged conflict, psychological or psychological factors, the sense of willingness to budge.Keywords: Mediation, Peace, Divorce Dispute, Supreme Court